Aplikasi teori katharine kolcaba pada pasien preoperasi mitral valve replacement: The application of katharine kolcaba’s theory in a preoperating mitral valve replacement patient - Antarika, Gde Yasa; Herawati, Tuti (Stikes Wira Medika Bali, 2021)
Mitral valve replacement (MVR) is a heart surgery procedure that is performed to replace a patient's mitral valve using an artificial heart valve among patients with moderate to severe mitral valve damage with symptomatic, or asymptomatic. Patients who undergo preoperative MVR might have experience including physical discomfort such as shortness of breath, fatigue, edema due to reduced mitral valve function. Patients also had psychological discomfort such as feeling anxious about the surgical procedure. The purpose of this study is to provide an overview of applying Katharine Kolcaba's theory of comfort to clients with preoperative MVR. The research method is a descriptive observational case study with a nursing care approach from the assessment stage, determining the diagnosis, planning, implementing actions, and evaluating one patient with preoperative MVR. The results of data analysis showed that the patient experienced physical discomfort in the form of decreased cardiac output, activity intolerance, and also psychological discomfort, namely anxiety. Comfort interventions are provided in the form of comfort standards, coaching, comfort food for the soul. The comfort theory of Katharine kolcaba is rightly applied to MVR preoperative nursing care which is characterized by a decrease in the anxiety scale, and the patient expresses his readiness to undergo surgery.